Profile of Problem-Solving Abilities on Elementary School Teacher Education Students in The Basic Mathematics Course - Anisah, Anisah; Sri Lastuti (Tinta Emas Publisher, 2024)
This research aims to describe the mathematical problem-solving abilities of first-semester students in the Elementary School Teacher Education Program at STKIP Taman Siswa Bima. It employs a quantitative descriptive research design. The subjects consist of Class IE students selected through purposive sampling, comprising 29 female students and 13 male students. Data collection involves a test method utilizing a Mathematical Problem-Solving Ability Test consisting of three essay questions. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results indicate that based on the analysis of the mathematical problem-solving ability test results, using the four-step Polya approach (understanding the problem, devising a solution plan, executing the solution plan, and reviewing the answer), students' ability to understand the problem falls into the